Erratum to simple pre-procedure risk stratification tool for contrast-induced nephropathy - Ni, Zhonghan; Liang, Yan; Xie, Nianjin; Liu, Jin; Sun, Guoli; Chen, Shiqun; Ye, Jianfeng; He, Yibo; Guo, Wei; Tan, Ning; Chen, Jiyan; Liu, Yong; et al. (Journal of Thoracic Disease, 2019)
Erratum to: J Thorac Dis 2019;11:1597-610